Engagement through play? The relationship between video games and political engagement - Wagner, Hanne Gesine (2020)
The presented research is an investigation of politics in video games. This is done with two overarching goals in mind. The first is to further the understanding of an under-researched area in both political science and game studies as well as human computer interaction. The second and main aim is to consider how games can be used to promote political engagement and increase the interest of the players in real world politics. Both goals were pursued using an interdisciplinary approach, introducing insights, methods and literature of Political Science and Political Psychology, with Human Computer Interaction and Game Design studies.